(3GdJaGhV (B:s (3egGQGJ hGSJQGJjLjGJ (B/s - (3GOQjS, KGHJ YHO GdQMeGfs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2001)
(3eaghe hCHYGO YedjI GdJaGhV,GdeaGgje GdCSGSjI ddJaGhV,GdCHYGO GdOjfGejcjI ddJaGhV,GdbhI hGdJCKjQ,EOGQI GdJaGhV,GdEYOGO hGdJNWjW,GdESJQGJjLjGJ hGdJcJjcGJ GdJaGhVjI,GdCHYGO GdJfXjejI,GdJfajP hGdJbjje(B-(3GdLhGfH GdSdhcjI ddJaGhV,feGPL GdSdhc GdGfSGfj hCfeGW TNUjI GdeaGhVjf,GdJfejI GdPGJjI ddeaGhV GdaYGds
(3HjHdjhZQGajG(B: (3U(B.497s
Keywords: (3GdEOGQIs; (3GdJaGhVs